Assessing the impact of energy R&D on green growth in OECD countries: a CS-ARDL analysis - Ashraf Galal Eid (16982736) (2024)
Since the introduction of the OECD innovation and green growth strategies in 2007 and 2011, respectively, the OECD countries have been actively engaged in supporting green energy R&D to accelerate the development of clean energy technologies. Specifically, the OECD recognizes that both renewable energy R&D and energy efficiency R&D are key components of a low-carbon and sustainable energy system. This study aims to assess the impact of disaggregated energy R&D on green growth in 21 high-income OECD countries, from 1990 to 2021. Two key green growth indicators, namely energy productivity and CO2 productivity, are used as response variables. The long-run CS-ARDL model results show that renewable energy R&D and fossil fuel R&D have a positive and significant impact on energy productivity in all model specifications, with renewable energy R&D exhibiting a relatively stronger impact compared to fossil fuel R&D. The long-run effects of the disaggregated energy R&D variables on CO2 productivity align with the results of the energy productivity model. Based on the study's findings, policymakers should consider reallocating the energy R&D budget towards renewable energy R&D, fostering international collaboration between OECD countries in renewable energy R&D, and implementing technology-specific policies to encourage investment in renewable energy technologies. Other Information Published in: Environmental Economics and Policy Studies License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10018-024-00413-4